Guideline for diagnosis, prophylaxis and treatment of invasive fungal infection post burn injury in China 2013. Issue 2 (6th April 2014) - Luo, Gaoxing; Tan, Jianglin; Peng, Yizhi; Wu, Jun; Huang, Yuesheng; Peng, Daizhi; Wang, Xu; Hu, Dahai; Xie, Songtao; Zhang, Guoan; Han, Chunmao; Huang, Xiaoyuan; et al.
Abstract: Invasive fungal infection is one of the major complication of severe burns which can induce local or systemic inflammatory response and cause serious substantial damage to the patient. The incidence of fungal infection for burn victims is increasing dramatically during recent years. This guideline, organized by Chinese Society of Burn Surgeons, aims to standardize the diagnosis, prevention and treatment of burn invasive fungal infection. It can be used as one of the tools for treatment of major burn patients.